Private and public investment in Malaysia: A panel time-series analysis - Hassan, Sallahuddin; Othman, Zalila; Abd Karim, Mohd Zaini (EconJournals, 2011)
Public capital hypothesis explains that a positive relationship exists between private and public investment. This paper examines the validity of the hypothesis by using a panel time series analysis on four sectors of the Malaysian economy (agriculture, industry and trade, transportation and communication, and construction). Panel co-integration analysis is used to prove the relationship between private domestic investment and public investment by using panel data for the period of 1976–2006.Two interaction variables, public investment and gross domestic product and investment and privatization policy were included as independent variables to take into account the influence of gross domestic product and privatization policy on the effect of public investment on private investment.Results of the study indicate that public investment has positive effect on private investment in all the three sectors except agricultural sector, suggesting that government expenditure encourage more private investment if focus is given towards productive expenditure.